Memahami Konsep Khiyar Sebagai Nilai Etika Bisnis Kontemporer - St Samsuduha; Ardi Ardi (Al-Tafaqquh: Journal of Islamic Law, 2022)
This paper reviews the specific concept of khiyar as one of the values of business ethics as prescribed in Islam. A contemporary business that tends to be free must be filled with ideal concepts related to business ethics. The concept of khiyar in Islam is essential to understand the understanding of the Muslim generation who will enter the business world, which is currently carried out openly. This study concludes that business ethics is an essential moral foundation to be put forward in business. In it, many ideal principles are problematic for humans who apply them. The ideal principles include the values of independence, fairness, profit, and moral integrity. Islam strongly dictates doing a profitable business. Therefore, in Islamic law, the term khiyar is known, which regulates the rights of buyers and sellers in doing business. The term khiyar has become a specific source of encouraging contemporary business ethics because it is very pro-beneficial in business synergies.